2013
DOI: 10.29176/2590843x.264
|View full text |Cite
|
Sign up to set email alerts
|

Características epidemiológicas y clínicas de las onicomicosis causadas por Fusarium spp. en un centro de referencia de Bogotá, Colombia, 2001-2010

Abstract: Introducción. Fusarium spp. es uno de los agentes etiológicos de onicomicosis por mohos no dermatofitos aislados con mayor frecuencia en todo el mundo. Sin embargo, la información disponible sobre el tema es limitada y algunas veces contradictoria, probablemente debido al escaso número de casos informados. El objetivo del estudio fue describir las características epidemiológicas y clínicas de un grupo de pacientes con diagnóstico confirmado de onicomicosis por Fusarium spp. en un centro de referencia de Bogotá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In South America and Europe, there are studies suggesting that Fusarium is an important cause of onychomycosis. 12,13 In 92 cases (41%) involving Candida species, C parapsilosis, C albicans, C famata, C lusitanea, C glabrata and C lipolytica were the most common pathogens, respectively, which is in accordance with many studies. 9,10 In cases of candidal onychomycosis, females (76.6%) were affected more than males (23.4%).…”
Section: Discussionsupporting
confidence: 86%
“…In South America and Europe, there are studies suggesting that Fusarium is an important cause of onychomycosis. 12,13 In 92 cases (41%) involving Candida species, C parapsilosis, C albicans, C famata, C lusitanea, C glabrata and C lipolytica were the most common pathogens, respectively, which is in accordance with many studies. 9,10 In cases of candidal onychomycosis, females (76.6%) were affected more than males (23.4%).…”
Section: Discussionsupporting
confidence: 86%
“…In other studies, onychomycosis has more often been diagnosed in women than men [12][13][14][15], a trend which might be skewed by gender differences, e.g., women are more likely to schedule dermatology appointments. Nevertheless, this variable was not statistically significant to our study, as reported by Diepeningen et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…In general, a prevalence of Fusarium in dermatological infections has been reported to range between 2 and 8 % [6][7][8], but this is particularly higher in Colombia, being estimated at 15-30 % [9][10][11][12][13]. In two studies, conducted in 2003 and 2009 in Medellín and Bogotá, respectively, Fusarium solani was the most frequent cause of onychomycosis, followed by Fusarium oxysporum and Fusarium verticillioides [14,15], although the distribution of Fusarium species in dermatological infections varies around the world.…”
Section: Introductionmentioning
confidence: 99%
“…In Colombia (South America), there are studies suggesting the Fusarium species as the most common. 8 , 9 In European countries, the most frequent species are: Scopulariopsis brevicaulis, Aspergillus sp., Acremonium sp. and Fusarium sp.…”
Section: Discussionmentioning
confidence: 99%